Analisis Penerapan Kebijakan Rekam Medis Elektronik (RME) terhadap Efektivitas Pelayanan Kesehatan di Puskesmas Koto Lolo Kota Sungai Penuh Tahun 2025 - Andre Eko Setiawani Andre Eko Setiawani; Subang Aini Nasution; Dewi Riastawaty (Lembaga Intelektual Muda (LIM) Maluku, 2026)
One method or technology used to improve the quality of health services at Community Health Centers in a sustainable manner in accordance with the objectives of implementing Community Health Centers in the community is to use Electronic Medical Records (RME) (Nurhayati & Muti, 2023). The regulations governing RME in Indonesia are as follows: Minister of Health Regulation Number 24 of 2022 concerning Medical Records is expected to be able to answer the challenges of health services in the field of technology. This type of research is quantitative research. This type of research aims only to find out whether there is an impact or effect produced by the independent research variable on the dependent research variable. This research was also carried out by making direct observations at the research location to collect data and then cross-checking the data that had been collected with the actual reality. This research will be carried out at the Koto Lolo Community Health Center, Sungai Banyak City. The population in this study were all users of the electronic medical record (RME) at the Koto Lolo Community Health Center, Sungai Banyak, a total of 84 officers. The research sample was all 84 users of electronic medical records (RME) who served at the Koto Lolo Community Health Center, Sungai Full City. The sampling technique is the total population where the researcher takes the entire population to become the research sample. The instruments used to collect data in this research were interview sheets, observation sheets and electronic medical record policies based on the Republic of Indonesia Minister of Health Decree 2022. The results of the research explained that there was an influence of the implementation of electronic medical record (RME) policies on the effectiveness of health services at the Koto Lolo Public Health Center, Sungai Full City in 2025 with a value of P = 0.003 Keywords: Electronic Medical Records (RME) Policy, Health Services